Oxidative stress model of lipopolysaccharide combined with thrombin inducing in broiler chicks - Shi, Huiyu; Yang, Fengyuan; Peng, Zeru; Wu, Junlong; Wang, Qin; Qiu, Pingfei; Bao, Ruiying; Huang, Liangmin; Li, Xiaochun; Zhang, Haiwen; Wang, Xuemei (Frontiers in Veterinary Science, 2024)
Lipopolysaccharides (LPS) are commonly used to construct inflammation models. However, poultry have a certain degree of tolerance to LPS due to the lack of thrombin XI and XII in their bodies. Thrombin activation produces clotting factors that can cleave prothrombin to form thrombin. The purpose of this study was to construct a chick oxidative stress model used different concentrations of LPS combined with thrombin in order to screen for the optimal concentration for constructing the oxidative stress model, and to explore the effects of this stimulus on various indicators of chicks. Eighty-one young chicks (4-days-old) were randomly divided into three groups with 27 chicks per group where each group contained 3 replicates with 9 birds each: a control group (physiological saline), a low-dose group (LPS 5 mg/kg thrombin 150 U/kg), and a high-dose group (LPS 10 mg/kg thrombin 300 U/kg). The results indicated that compared with the control group, the low-dose group and the high-dose group significantly increased the content of Malondialdehyde (MDA) in serum and reduced the content of T-AOC, GSH-PX and SOD, respectively. Meanwhile, the levels of NO and inflammatory factors IL-1β, IL-6 and TNF-α TNF-α in the liver were significantly increased in the low-dose and high-dose groups compared with the control group, respectively. Liver and thymus tissue sections from the low- and high-dose groups showed hemorrhage, hemolysis, and a small amount of exudation. In terms of inflammatory effect, the serum MDA content and the levels of NO, IL-1β, IL-6 and TNF-α factors in the liver were significantly increased in the low-dose group compared with the high-dose group. On histopathological observation, tissue damage was more pronounced in the low-dose group than in the high-dose group. In conclusion, LPS combined with thrombin could induce oxidative stress in chicks and the pathological changes of the low-dose effect are more pronounced.